2017
DOI: 10.1039/c7cp01063j
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of glassy GeTe4by first-principles molecular dynamics

Abstract: A transient thermal regime is achieved in glassy GeTe by first-principles molecular dynamics following the recently proposed "approach-to-equilibrium" methodology. The temporal and spatial evolution of the temperature do comply with the time-dependent solution of the heat equation. We demonstrate that the time scales required to create the hot and the cold parts of the system and observe the resulting approach to equilibrium are accessible to first-principles molecular dynamics. Such a strategy provides the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…We consider now the set of PBC, involving ITRs, in Eqs. (13), (14), (15), and (16). In the present non-local formulation, the heat flux reads…”
Section: Appendix B2 Periodic Boundary Conditions For a Bilayer Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider now the set of PBC, involving ITRs, in Eqs. (13), (14), (15), and (16). In the present non-local formulation, the heat flux reads…”
Section: Appendix B2 Periodic Boundary Conditions For a Bilayer Systemmentioning
confidence: 99%
“…AEMD has been applied by several authors to the calculation of the thermal conductivity in c-Si,c-Ge and α-quartz [1], in Si/Ge nanocomposite [9], in Si nanowires [10] and in graphene-based structures [11,12]. Initially developed for classical Molecular Dynamics (MD) this technique has been recently implemented in ab-initio calculations as well [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, given the high computational cost of the Green-Kubo [9] or direct methods [10], FPMD have to be combined with more tractable, alternative approaches. With this purpose in mind, we calculated via FPMD the thermal conductivity of a disordered material (glassy GeTe 4 ) [11] by taking advantage of the approach-to-equilibrium molecular dynamics (AEMD) methodology [12]. In this first joint application of FPMD and AEMD, we showed that the inherent time intervals are within the reach of FPMD, in spite of a substantial temporal relaxation from an out-ofequilibrium situation (phase 2 of AEMD) featuring two adjacent parts of a periodic volume kept at different temperatures (phase 1 of AEMD).…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that controlled irradiation (with He ions) has been used to lower the lattice thermal conductivity of Si nanowires. 38 In a recent AEMD study for a related glassy chalcogenide material, namely GeTe 4 , the authors reported a value of 0.013±0.003 W K −1 m −1 for the thermal conductivity, 39 which is an order of magnitude lower than the experimental measurement for this material (0.1 W K −1 m −1 ). 40 This discrepancy is likely due to the small model system size (185 atoms), which illustrates the limitations of tractable ab initio molecular-dynamics simula-tions.…”
mentioning
confidence: 83%
“…Non-equilibrium methods require careful consideration of finite-size effects and they can no longer be easily applied to materials with a higher thermal conductivity, or with a longer mean-free path, especially at low temperature. Nevertheless, long-wavelength modes and quantum effects are not significant in glassy Ge 2 Sb 2 Te 5 at 300 K. 8,39 While not a substitute for analysing the finite-size effects, the influence of the boundary-region Langevinthermostat damping time was included in our estimates of the lattice thermal conductivity and is discussed in the Supplemental Material.…”
mentioning
confidence: 99%